Determination of the axial and radial fibre stress distributions for the Broutman test - Sinclair, R.; Young, R.J.; Martin, R.D.S. (Composites science and technology, 2004)
Composite micromechanics has been a subject of considerable interest over the past 25 years. Most research has been concerned with single-fibre composite specimens and the distribution of axial fibre stress or strain. The main parameter of interest is normally the interfacial shear stress that characterises the conditions for the breakdown of the fibre/matrix interface. Over recent years significant advances have been made through the use of Raman and/or fluorescence microscopy to map the distribution of axial stress and strain along the fibres. This paper reports the development of fluorescence microscopy to enable both axial and radial fibre stresses to be determined in alumina single crystal fibres embedded in epoxy resins. This is demonstrated for the Broutman test in which the fibre/matrix interface is subjected to significant levels of transverse radial stress. The micromechanics of reinforcement by single crystal and polycrystalline alumina fibres is contrasted. Important new insights into the processes that initiate breakdown of the fibre/matrix interface are evaluated.